Enhancing Early Childhood Recognition of Three-Dimensional Shapes Through Augmented Reality Media Using the Assemblr Edu Application - Febriani, Tri Mustika; Choiriyah, Choiriyah; Widiyastuti, Arie (CV. Creative Tugu Pena, 2025)
This study aims to determine the effectiveness of using Augmented Reality (AR)-based media through the Assemblr Edu application in improving the recognition of three-dimensional shapes among early childhood learners. The research method employed was Classroom Action Research (CAR) using the Kemmis & McTaggart model, consisting of pre-cycle, cycle I, and cycle II. The research subjects were 20 children in group A (ages 4–5 years) at TK Sahabat Bekasi. The research instruments included a Lesson Plan, observation sheets, and interviews. The results showed an improvement in children’s understanding of three-dimensional shapes. In the pre-cycle stage, the average achievement was only 20.77%, which increased to 42.85% in cycle I, and reached 87.00% in cycle II, exceeding the success criterion of >80%. These findings demonstrate that the use of AR through the Assemblr Edu application can effectively enhance early childhood learners’ understanding of three-dimensional shapes in a more interactive and enjoyable way.